Ответы и объяснения

2013-01-31T15:05:30+00:00

№1 Найдите значение выражения:

 

a)\sqrt[3]{216} + \sqrt[3]{2\frac{10}{27}} = \sqrt[3]{27*8} + \sqrt[3]{\frac{64}{27}} = \sqrt[3]{3^{3}*2^{3}} + \sqrt[3]{\frac{4^{3}}{3^{3}}} =3*2 + \frac{4}{3} = 6 + \frac{4}{3} = \frac{6\times3+4}{3} = \frac{18+4}{3} = \frac{22}{3} = 7\frac{1}{3}

 

b)2\sqrt[3]{3}+\sqrt[3]{81}-\sqrt[3]{\frac{3}{8}} = 2\sqrt[3]{3}+\sqrt[3]{3^{4}}-\sqrt[3]{\frac{3}{2^{3}}} = 2\sqrt[3]{3}+3\sqrt[3]{3}-\frac{\sqrt[3]{3}}{2}\= \frac{4\sqrt[3]{3}+6\sqrt[3]{3}-{\sqrt[3]{3}}}{2} =\frac{\sqrt[3]{3}(4+6-1)}{2}=\frac{9\sqrt[3]{3}}{2}=4,5\sqrt[3]{3}}

 

 

№2 Упростите выражение:

 

a)\sqrt[3]{a^{2}}(6\sqrt[3]{a}-\sqrt[3]{125a^{7}})=\sqrt[3]{a^{2}}\sqrt[3]{a}(6-\sqrt[3]{5^{3}a^{6}})=\sqrt[3]{a^{3}}(6-5\sqrt[3]{a^{6}})=a(6-5a^{2})

 

 b)(\sqrt[3]{a} +2)(\sqrt[3]{a^{2}} - 2\sqrt[3]{a}+4) =\sqrt[3]{a}^{3} +2^{3}=a+8

 

\\\\\ В данном случае используется формула сумма кубов:

 

a^{3}+b^{3} = (a+b)(a^{2}-ab+b^{2})